(untitled) (Journal of Asian Development Studies, 2020)
In today world, companies have to adopt proper financial strategies in order to use capital in an optimal way and can never overlook costs related to limited financial repair of capital in their planning. Performance evaluation shows the success level of organizations in achieving their objectives and performance is closely related too company objectives. Generally, the performance of companies may be evaluated in three levels: efficient non-effective and economic benefit and capability; efficiency indicates the level of achieving objectives and doesn’t regard how the activity is performed; efficiency relates to the way of achieving goals and choosing the suitable methods to use resources in order to limit the related charges. Economic benefit and capability is using resources efficiently regarding it profitability in long- term. In this study, economic benefit and arability are considered and according to that the aim of institution should be creating added value (economic value) or utilizing the existing resources in the business unit, so different criteria are presented for evaluation: sale amount, profit of each share (EPS), return of investment (ROI), return of share owners emolument (ROE) which all are traditional criteria for measuring company performance questioned by the accounting information in efficient market and different existing accounting methods.